Public Relations Management in Increasing the Number of Students in Islamic Boarding School - Muhammad Ghafar; Zayyinah Haririn (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
Public relations management serves as a strategic tool for managing communication between Islamic boarding schools and their stakeholders, so that the educational institution's objectives can be achieved effectively and efficiently and increase the number and competitiveness of students in terms of both quality and quantity. This study aims to analyze the concept of PR planning in increasing the number of students, PR implementation patterns, and PR evaluation models at the Darul Muttaqin Islamic Boarding School. The study uses a qualitative descriptive approach with a case study type. Data were collected through direct observation, semi-structured interviews with boarding school administrators and staff, and documentation of PR programs and activities. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and conclusion drawing/verification. The results of the study show that Islamic boarding schools conduct comprehensive needs analyses, set goals in line with their targets, and implement routine and incidental programs to increase the number of students. These programs include regular Saturday Legi announcements to internal and external parties, socialization of new student admissions through social media, the formation of a WhatsApp group for parents, art performances and achievement exhibitions at parent meetings, and the development of diplomatic relations, including cooperation with the Japanese Consul General. In addition, observation of the implementation of public relations programs, absorption of aspirations from stakeholders, as well as managerial supervision and human resource development also support the effectiveness of the program.